2009
DOI: 10.4103/0972-0707.55621
|View full text |Cite
|
Sign up to set email alerts
|

Management of intrusive luxation with immediate surgical repositioning

Abstract: Intrusive luxation is one of the most severe forms of traumatic injuries in which the affected tooth is forced to displace deeper into the alveolus. As a consequence of this type of injury, maximum damage occurs to the pulp and all the supporting structures. This report presents a case of severe intrusive luxation of mature maxillary central and lateral incisor in a 40-year-old male. The intruded tooth was immediately repositioned (surgical extrusion) and splinted within hours following injury. Antibiotic ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Higher incidence of resorption was also observed in case of endodontic treatment being performed prior to extrusion due to contamination by serum, blood, and saliva . Various other case reports and case series have shown no signs of root resorption after an average follow up of 1 year . Periapical pathologies and marginal bone height:‐ Normal periapical healing and resolution of radiolucency was seen in almost all reported case reports and case series . A study showed a minor loss of marginal bone height in one out of the 20 teeth treated .…”
Section: Resultsmentioning
confidence: 96%
“…Higher incidence of resorption was also observed in case of endodontic treatment being performed prior to extrusion due to contamination by serum, blood, and saliva . Various other case reports and case series have shown no signs of root resorption after an average follow up of 1 year . Periapical pathologies and marginal bone height:‐ Normal periapical healing and resolution of radiolucency was seen in almost all reported case reports and case series . A study showed a minor loss of marginal bone height in one out of the 20 teeth treated .…”
Section: Resultsmentioning
confidence: 96%
“…Among all the types of luxation injuries, intrusion injury is the rarest one. [ 9 ] The treatment of intruded permanent incisors can be challenging. If the tooth is intruded 3–7 mm, surgical (preferably) or orthodontic repositioning is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…If root canal treatment is not initiated during these weeks, external root resorption may occur. The primary reason why we chose surgical extrusion as a treatment option was that it could allow rapid positioning ( 11 ) to initiate root canal treatment in which the tooth was totally embedded in the alveolar bone in late applied cases. Also, the second case was presented with teeth of multiple intrusion injuries and, re-positioning by surgical extrusion in the first three weeks after trauma is recommended.…”
Section: Discussionmentioning
confidence: 99%